Overdiagnosis of Attention-Deficit/Hyperactivity Disorder in Children and Adolescents: A Systematic Scoping Review - Kazda, Luise (JAMA Netw Open, 2021)
IMPORTANCE: Reported increases in attention-deficit/hyperactivity disorder (ADHD) diagnoses are accompanied by growing debate about the underlying factors. Although overdiagnosis is often suggested, no comprehensive evaluation of evidence for or against overdiagnosis has ever been undertaken and is urgently needed to enable evidence-based, patient-centered diagnosis and treatment of ADHD in contemporary health services. OBJECTIVE: To systematically identify, appraise, and synthesize the evidence on overdiagnosis of ADHD in children and adolescents using a published 5-question framework for detecting overdiagnosis in noncancer conditions. EVIDENCE REVIEW: This systematic scoping review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) Extension for Scoping Reviews and Joanna Briggs Methodology, including the PRISMA-ScR Checklist. MEDLINE, Embase, PsychINFO, and the Cochrane Library databases were searched for studies published in English between January 1, 1979, and August 21, 2020. Studies of children and adolescents (aged ≤18 years) with ADHD that focused on overdiagnosis plus studies that could be mapped to 1 or more framework question were included. Two researchers independently reviewed all abstracts and full-text articles, and all included studies were assessed for quality. FINDINGS: Of the 12 267 potentially relevant studies retrieved, 334 (2.7%) were included. Of the 334 studies, 61 (18.3%) were secondary and 273 (81.7%) were primary research articles. Substantial evidence of a reservoir of ADHD was found in 104 studies, providing a potential for diagnoses to increase (question 1). Evidence that actual ADHD diagnosis had increased was found in 45 studies (question 2). Twenty-five studies showed that these additional cases may be on the milder end of the ADHD spectrum (question 3), and 83 studies showed that pharmacological treatment of ADHD was increasing (question 4). A total of 151 studies reported on outcomes of diagnosis and pharmacological treatment (question 5). However, only 5 studies evaluated the critical issue of benefits and harms among the additional, milder cases. These studies supported a hypothesis of diminishing returns in which the harms may outweigh the benefits for youths with milder symptoms. CONCLUSIONS AND RELEVANCE: This review found evidence of ADHD overdiagnosis and overtreatment in children and adolescents. Evidence gaps remain and future research is needed, in particular research on the long-term benefits and harms of diagnosing and treating ADHD in youths with milder symptoms; therefore, practitioners should be mindful of these knowledge gaps, especially when identifying these individuals and to ensure safe and equitable practice and policy.